Konflik Sosial Dalam Novel Tiba-Tiba Malam Karya Putu Wijaya: Kajian Sosiologis - Dara Windiyarti (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
This study aims to describe the social conflicts in the novel Tiba-tiba Malam by Putu Wijaya. The dataof this study was taken from the novel Tiba-tiba Malam by Putu Wijaya published in 2005 by CompassPublisher. Data collection was done by using literature method. This study used Geoerge Simmel andRalf Dahrendorf theory of conflict. The method used in this study is descriptive analysis. This studyaims to reveal the social conflicts between characters and the social conflicts between characters andthe villagers, the causes of conflicts and actions to resolve the conflicts. This research resulted in thefollowing. First, the emergence of conflict between Sunatha family and Utari family was motivated bypersonal issues, while the emergence of conflict between Sunatha family and the villagers wasmotivated by customs violations. Secondly, the causes of individual conflicts are the individualbehavior and the economy, while the cause of conflicts with the villagers is the strong kinship amongthe villagers. Thirdly, the action to solve the conflicts is to do a good communication between partiesin conflicts.